Judicial Sentencing Factors for Parental Child Sexual Abuse at Tilamuta District Court - Juan Wahyudi FP Pagau; Lisnawaty Wadju Badu; Muhamad Khairun Kurniawan Kadir (Yayasan Cahaya Generasi Positif, 2026)
Legal enforcement concerning parental child sexual abuse frequently triggers a sharp clash of norms between rigid procedural certainty and substantive justice. This article examines the judicial reasoning within Tilamuta District Court Decision Number 14/Pid.Sus/2024/PN Tmt, where judges exercised progressive judicial activism by rendering an ultra petita sentence, intentionally increasing the penalty from twelve to seventeen years of imprisonment. This empirical study demonstrates that the step-parent’s asymmetrical domestic power relation fundamentally distorts material evidence, thereby neutralizing the victim's defensive capacity and necessitating extraordinary judicial intervention. Consequently, this article explicitly proposes the formulation of specialized sentencing guidelines as ius constituendum securely grounded in therapeutic jurisprudence principles. These guidelines offer a structured, measurable matrix to legitimize progressive judicial discretion, transforming absolute domestic authority into an absolute aggravating factor while mandating longitudinal forensic psychological assessments. Ultimately, this proposed model successfully transitions the judiciary from mechanical statutory application toward a highly victim-oriented restorative justice framework.